American Indian Health in South Dakota-A Health Systems Case - Matthew Tobey; Chana Sacks; Daniel Foster; Dennis Norman; Susan Karol; Patrick Lee (Association of American Medical Colleges, 2014)
Abstract Introduction This resource teaches health professionals about health systems by exploring one with unique, pressing challenges. The primary goal is for learners to develop the analytic skills to understand the health system, thereby allowing them to propose suggestions for reform. The case also offers a window into health for Native populations and underserved rural populations, neither of which are often included in health care curricula. This resource is intended for use by any group of health professionals. The material was originally designed to be used with first-year medical residents. Methods The resource includes a 3-hour business school-style case study teaching principles in health systems and health systems strengthening through the example of two struggling Indian Health Service sites in South Dakota. The session is designed for 15-20 learners but could be taught with a smaller or larger group. Included in the resource are an instructor's guide, a teaching note, a group problem-solving activity, and the case study itself. Central issues include health disparities, social determinants of health, rural health, Native health, and health systems reform. The resource features a number of innovations, including a journalistic style, a health systems problem without an obvious solution, and a grounding of the case in a learner perspective. Results The case has been taught twice annually to internal medicine interns. Learner reviews were positive. The group session was well liked and its length extended in the second year. Discussion The case's difficulty should be considered before teaching. It challenges learners by requiring both analysis and some novel thinking. The case study document might be used alone in various settings. It is possible that simpler teaching methods (e.g., didactics) might be more successful for beginner learners.